DIAGNOSIS OF COXITIS IN ANKYLOSING SPONDYLOSIS - T. V. Dubinina; A. B. Dyomina; A. V. Smirnov; Sh. F. Erdes (Научно-практическая ревматология)
Coxitis is one of the characteristic clinical manifestations of ankylosing spondylitis (AS). Hip joint (HJ) damage in AS is regarded as a poor prognostic factor and the early detection of coxitis is of great importance, as timely adequate therapy may reduce the risk of irreversible HJ changes. Coxitis may be diagnosed clinically and using different imaging techniques, each of which can characterize different aspects of damage of these joints. The lecture considers the clinical and instrumental diagnosis of coxitis in AS.